Self-Reported Health in Patients on or at Risk of Sick Leave Due to Depression and Anxiety: Validity of the EQ-5D - Sandin, Kenneth; Shields, Gemma E.; Gjengedal, Ragne G. H.; Osnes, Kåre; Bjørndal, Marianne Tranberg; Hjemdal, Odin (Frontiers in Psychology, 2021)
Objectives The EQ-5D is a generic, self-report measure of health that is increasingly used in clinical settings, including mental health. The EQ-5D captures health using five dimensions: Mobility, Self-care, Usual activities, Pain/discomfort, and Anxiety/Depression. The validity of the EQ-5D is previously unexplored in patients on or at risk of sick leave due to depression and anxiety. The study’s aim was to examine its validity in this group of patients. Methods Baseline data were collected from self-report questionnaires in an observational study (N = 890) at a Norwegian outpatient-clinic. Participants were adults on or at risk of sick leave due to depression and anxiety who were referred for treatment by general practitioners. The crosswalk methodology was applied to estimate the EQ-5D value. Validity was assessed by comparing responses on the EQ-5D with the Beck Depression Inventory-II (BDI-II), the Beck Anxiety Inventory (BAI), and Subjective Health Complaints (SHC). An ordinal regression model was used to assess known-groups validity. Convergent validity was assessed using Pearson’s correlation coefficient, and a multivariate regression model that included sociodemographic characteristics. Results The mean EQ-5D value was .631, indicating reduced health status compared to “full health” anchored at 1.0, and patients reported moderate levels of depression and anxiety. Ordinal regression indicated that the EQ-5D could discriminate between different levels of symptom severity for depression and anxiety. The EQ-5D value showed significant correlation with the clinical measures; r = -.52 for the BDI-II, r = -.49 for the BAI, and r = -.44 for SHC. The multivariate regression showed that the clinical variables significantly predicted the EQ-5D value, explaining 40.1 % of the variance. Depression and anxiety scores were the largest determinants of EQ-5D value, respectively, whilst sick leave, subjective health complaints, and gender made moderate contributions. Conclusion The EQ-5D showed indication of validity in patients on or at risk of sick leave due to depression and anxiety in the present study. The EQ-5D value was sensitive to both symptom severity and functional impairment in the form of sick leave. The findings support the EQ-5D as a feasible and relevant measure of health status in these patients.